2017
DOI: 10.1242/jeb.154583
|View full text |Cite
|
Sign up to set email alerts
|

Caspase-3 and GFAP as early markers for apoptosis and astrogliosis in shRNA-induced hippocampal cytotoxicity

Abstract: Genetic manipulation of cells and tissue by RNA interference has significantly contributed to the functional characterization of individual proteins and their role in physiological processes. Despite its versatility, RNA interference can have detrimental side effects, including reduced cell viability. We applied recombinant adenoassociated viruses by stereotaxic injection into the murine hippocampus to express different short hairpin RNA (shRNA) constructs along with eGFP. Tissue responses were assessed immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 24 publications
(32 reference statements)
2
11
0
Order By: Relevance
“…The pathway is dominated by a bcl-2 family members that regulate the release of cytochrome-c from the mitochondria then activate caspase protease that dismantle cells to make apoptosis formation and signal efficient phagocytosis of cell corspses. [1718] It is consistent with the previous study which showed that annonacin from Annonaceae family induces the apoptotic cell death in a caspase-3 related to the pathway on endometrial cancer cells. [19]…”
Section: Discussionsupporting
confidence: 90%
“…The pathway is dominated by a bcl-2 family members that regulate the release of cytochrome-c from the mitochondria then activate caspase protease that dismantle cells to make apoptosis formation and signal efficient phagocytosis of cell corspses. [1718] It is consistent with the previous study which showed that annonacin from Annonaceae family induces the apoptotic cell death in a caspase-3 related to the pathway on endometrial cancer cells. [19]…”
Section: Discussionsupporting
confidence: 90%
“…One of the apoptosis marker in the early stage is showed by caspase-3 expression. 17,18 In this study, other compounds of Annona squamosa like flavonoid, alkaloid and saponin triggered ROS production that induced apoptosis through actions at different signal transduction pathways such as cyclin-dependent kinases (CDKs), caspases, Bcl-2 family members, epidermal growth factor (EGF)/epidermal growth factor receptor (EGFR), phosphatidylinositol-3-kinase/Akt, MAPK and NF-κB, which may affect cellular function by modulating genes or phosphorylating proteins. 19 The result of caspase-3 expression in immunocytochemistry shows that the increasing doses followed by the increasing amount of caspase-3 expression.…”
Section: Acknowledgementmentioning
confidence: 93%
“…To gain further insight into the mechanism accompanying the loss of the CA1 pyramidal cell layer in sh2-treated mice, we used active (cleaved) caspase-3 (Caspase) and glial fibrillary acidic protein (GFAP) as indicators for the adverse tissue responses [26] (Figure 6). At 5 weeks post-injection, fluorescent signals of active caspase-3, a main component of apoptosis in eukaryotic cells [27], was very high, especially in the CA1 subfield of sh2-injected hippocampi compared to shScr-injected hippocampi (Figure 6, upper panel).…”
Section: Molecular and Immunological Analyses Of Hcn2 Knock-downmentioning
confidence: 99%